Prevalence of superficial Mycosis in children of elementary schools, Babol, 2003-04 - SM Rezvani (Babol University of Medical Sciences, 2006)
BACKGROUND & OBJECTIVE: Superficial mycoses are the most common infection in Iran. Scalp mycoses are most frequently seen in children especially in elementary schools. The purpose of this study was to determine the prevalence of superficial mycoses in children of elementary schools.METHODS: In this descriptive study, among 20000 elementary school students in Babol, 2100 were randomly assessed during 2003-2004. Cluster sampling was used in schools. Students were clinically examined for fungal infections of hair, skin and nail and sampling was taken from suspicious cases. Direct microscopic and culture examination of samples were performed.FINDINGS: Among 2100 students, 136 cases (6.5%) had skin lesion. Fungal infection was seen in 35% after the microscopic and cultural examination. There were four cases of tinea versicolor (0.2%), 2 cases of periungal candidiasis (0.1%) and 1 case of tinea capitis (0.05%) caused by microsporum canis.CONCLUSION: According to the result of this study, superficial fungal infections are seen less among elementary school students.